Kampanye “Isi Piringku” Dan Penerapan Infused Water Sebagai Upaya Pencegahan Stunting Dari Masa Kehamilan - Rini Rahmayanti; Fitri Wahyuni; Darmaji Efrad; Miranda Sari; Siti Afifah; Fatmatul Zahra (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Andalas sub-district had the highest number of pregnant women in the last three months compared to other sub-districts, namely 185 people with complications of anemia and chronic energy deficiency (CED) of 37 people (20%). Judging from the nutritional status of children under five, the incidence of stunting in this area is still high, namely around 25%, consisting of children under five in the underweight (8.5%), malnourished (7.1%) and stunted (9.4%) categories. . In pregnant women, it was found that education about the nutrition of pregnant women had not been optimal, previously related to the nutrition of pregnant women and the "fill my plate" program, there was still low knowledge of pregnant women about the use of complementary therapies to overcome problems, especially nausea and vomiting, in order to maintain nutritional intake during pregnancy. The activity was carried out using the "fill my plate" campaign method and the application of infused water in RW 05, Andalas Village, targeting 15 pregnant women. The results of the pretest scores obtained the lowest score of 6 and the highest score of 12. The posttest score obtained the lowest score of 15 and the highest score of 19. The average score of the pretest was 9.2 and the posttest was 16.5. These results indicate that there is an increase in knowledge. The results of this community service activity include an increase in mothers' knowledge regarding balanced nutrition "fill my plate" and the application of infused water as an effort to prevent stunting during pregnancy.